Backlash against posters of BRAC's human rights & legal education program - Rafi, Mohammad; Ahmed, Shah Asad (BRAC Research and Evaluation Division (RED), 2019)
The Human Rights and Legal Education program of BRAC was initiated with the assumption that if the legal awareness of its clients was raised they would be able to protect themselves· from illegal, unfair or discriminatory practices in the villages. But it was observed that the rights of these clients were in occasions infringed because those who infringed the rights were themselves not legally aware. Thus, BRAC was convinced to believe that the rights of its clients would be better protected by raising the legal knowledge of the non-clients. As a result, the HRLE program added a poster component to its activities. In April 1997 the HRLE program took up a policy of fixing a 7-set poster in the villages and in the towns within the BRAC activity areas. The posters pictographically and in writing presented some of the legal rights and duties of the citizens of Bangladesh and indicated what could be the consequences of 'Violating those rights. Some 700,000 posters were posted so far. This venture was not without a hitch. Some in the community reacted against the posters. These backlashes have encouraged us to conduct this study. The objectives of this study were to: (1) investigate nature of backlashes; (2) find out how the Rural Development Programme (RDP) field staff handled the backlashes; and (3) investigate the causes for backlashes. A qualitative approach was adopted in conducting this study. The study was conducted in the catchment of RDP areas in Kuliarchar, Sharail, Kachikaia and Puthia. Data were collected based on checklists through individual and group interviews. The interviewees included RDP, RDP's village organization (VO) members, people working living at the 'Vicinity of the spot where posters were fixed, and local influential. The backlashes included verbal condemnation against the posters, tearing down the posters, teasing and rebuking BRAC staff for fixing posters and organizing demonstration against the poster program. The reaction of RDP offices against the backlashes varied from area to area. Its staff did not make any effort to prevent the ripping off the posters. In the case of organized and not severe backlash BRAC tried to convince those who reacted against the posters but where the backlash was severe BRAC compromised with them. The RDP staff took a pragmatic step against the backlashes in order to avoid any has done to the smooth functioning of the Program and for the success of postering in the long run.